Museum augmented interface for historical scale models: towards a new way for cultural heritage promotion - Hervy, Benjamin; Laroche, Florent; Kerouanton, Jean-Louis; Bernard, Alain; Courtin, Christophe; Guillet, Bertrand; D’haene, Laurence; Waels, Arnaud (International Journal of Virtual Reality, 2015)
In this paper, we describe an interactive museum application dedicated to historical scale models. This comes from a joint work between multidisciplinary teams: industrial engineering researchers, historians, museum curators and interactive interface designers. We present here the result of the project, based on scientific methodology. Results include system architecture, hardware and software, some use cases and user evaluation figures. This paper also underlines some methodology issues that illustrate future possibilities.